The pass-through from depreciation to inflation: Chile 1986-2001 - Noton, Carlos (Estudios de Economía, 2016)
A microeconomic model of imperfect Cournot competition is used to derive an explicit endogenous relationship between price level and the nominal exchange rate. We obtain a mark-up that varies endogenously with consumer real income. Using the model, the estimated pass-through –namely the impact of devaluation on inflation– ranges between 9-11% in the short run and between 21-32% in the long run for the period 1986-2001. However, the data supports a structural change in 1991, after which the pass-through coefficient declines significantly. Moreover, contrary to conventional wisdom, we find no evidence of procyclical pass-through.